A comparative utilisation of high dietary copra and palm kernel cakes-based diets with exogenous enzyme by young pullets and layers - diarra, siaka seriba (Indian Journal of Animal Nutrition, 2018)
The effects of enzyme supplementation of copra cake (CPC) and palm kernel cake (PKC) in growing pullets and laying hens were investigated in two experiments. In experiment 1 a control diet based on fish meal and soybean meal and 4 diets containing 200 g CPC or PKC/kg with and without exogenous enzyme were fed each to 3 replicate pens containing 10 growing pullets for a period of 70 days. In experiment 2 diets formulated as in experiment 1 were fed each to 10 point of lay birds for a period of 84 days. Pullets fed CPC and PKC based diets consumed more feed and water than the control (P<0.05). Feeding CPC and PKC without enzyme resulted in a poorer feed conversion efficiency (P<0.05). The laying hens showed no treatment difference in feed and water intake, feed conversion efficiency, Haugh unit and shell thickness (P>0.05) but hen-day production, egg weight and egg mass were improved with enzyme supplementation of the test materials (CPC and PKC). It was concluded that when diets are formulated on digestible amino acid and enzyme supplementation both PKC and CPC can be fed with advantage to egg-type birds. Feeding 200g CPC or PKC/kg diet depresses efficiency of feed utilisation in growing pullets but this adverse effect is overcome by challenzyme supplementation. In laying hens, challenzyme supplementation improves hen-day production but has no effect on the efficiency of feed utilisation. Further research on enzyme type and level is recommended.